A Systematic review of Mobile cloud computing Applications and its impact on Learning and Big data (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Mobile devices play a necessary role in our daily life, which are increasingly being used in different fields. Because of the high usage rate of mobile devices, the user needs safe technology to connect to big data exchange. That is presented by Mobile Cloud Computing (MCC), which happens by integrating mobile and cloud computing. This study shows the role of MCC and big data investigation in education. This holds extraordinary guarantee for the future because it has benefits like Cost less, Easily accessed, Huge Storage, Sharing, Collaborative interactions, resources availability, and Flexibility. Also, it haschallenges regarding Mobile network conditions, Control of applications Security, and privacy. We did a reference review of several studies related to mobile Education and its Potentials and Challenges. Also, we study the effect of MCC in boosting teaching and learning activities by 250 questionnaires for 150 teachers and 100 students and conducted a statistical study of using MCC for employee’s online courses in a year at El- Kenouz Training Centre in Qena, Egypt.